ANALYSIS OF INFLECTIONAL SUFFIX ON SELECTED POEMS BY ROBERT FROST - Nurkhamidah Putri Wulandari; Lilia Indriani (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2021)
As a language learner, definite changes or forms of words are significant. When a word is added by one or a few letters, the meaning and purpose of that word will change. Words changes occur due to the addition of letters at the beginning or the end of the word. The affix at the beginning of the word is called a prefix, while the affix at the end is called a suffix. Eight suffixes in English do not change the part of a word's speech but signify additional information about it; -s, 's, -'s, -er, -ed, -ing, -en, -est. This paper aims to Identify the most used inflectional suffixes in Robert Frost's poems, which are widely used in linguistics and literature study. The result of the research is that Robert Frost's poems use the entire inflectional suffixes. The -s suffix is the inflectional suffix that he uses the most in his poems. It indicates that Robert Frost tends to express or describe something in the plural form.